DIFFERENTIAL DIAGNOSIS OF ATYPICAL MODERN ENCEPHALOMYELITIS OF UNKNOWN CAUSE - Ch. Naydenov; Y. Argirova; T. Manolova; L. Manchev (Trakia Journal of Sciences)
To this day, there are cases of neuro infections that cannot be etiologically specified and are cured empirically. Clinics are difficult, and the healing process is prolonged with risks of complications. It is not uncommon for diseases to remain unrecognized for a long time due to an atypical clinical picture. This leads to prolonged exposure of the patient to the harmful effects of infection and prolongation of the disease process. The result is many costly studies without results. It is necessary to revise the current course of neuro infections and their classification, as well as to share information in specially created platforms for searching for coincidence and exchange of experience. In this regard, we present one of our cases, which remained undiagnosed and we find it interesting. The presented clinical case is atypical and etiologically unproven. An example of a challenge in diagnosis and treatment, that bears no resemblance to the relatively rare neuro infections in our region. We have studied the current changes and course of some of the most common encephalitis and summarized them with an aim to do the differential diagnosis. We need a revision of the current course of neuroinfections and a new classification based on the clinical picture.